Marcus theory for outer-sphere heterogeneous electron transfer: Predicting electron-transfer rates for quinones - Rees, N; Clegg, A; Klymenko, O; Coles, B; Compton, R (2004)
Steady-state voltammetry is used to measure the heterogeneous electron-transfer rates for the reduction of quinones to determine the dependence of k0 on molecular size, according to Marcus theory. This dependence is then used to predict the electron-transfer rate constants of related quinones, and the predictions are compared to experimental measurements.